1990
DOI: 10.1021/bi00455a029
|View full text |Cite
|
Sign up to set email alerts
|

Hairpin structures in DNA containing arabinofuranosylcytosine. A combination of nuclear magnetic resonance and molecular dynamics

Abstract: Nuclear magnetic resonance (NMR) and model-building studies were carried out on the hairpin form of the octamer d(CGaCTAGCG) (aC = arabinofuranosylcytosine), referred to as the TA compound. The nonexchangeable protons of the TA compound were assigned by means of nuclear Overhauser effect spectroscopy (NOESY) and correlated spectroscopy (COSY). From a detailed analysis of the coupling data and of the NOESY spectra the following conclusions are reached: (i) The hairpin consists of a stem of three Watson-Crick ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 51 publications
3
54
1
Order By: Relevance
“…The latter finding contradicts the results of earlier computational simulations that suggested a preference for the C2′-endo pucker by arabinose (22). Although the above experimental data are consistent with similar conformational tendencies by FANA and ANA, the conformation of ANA was demonstrated to vary significantly depending on the geometry of the parent duplex (23)(24)(25)(26)(27)(28)(29).…”
contrasting
confidence: 71%
“…The latter finding contradicts the results of earlier computational simulations that suggested a preference for the C2′-endo pucker by arabinose (22). Although the above experimental data are consistent with similar conformational tendencies by FANA and ANA, the conformation of ANA was demonstrated to vary significantly depending on the geometry of the parent duplex (23)(24)(25)(26)(27)(28)(29).…”
contrasting
confidence: 71%
“…At this point, it is interesting to compare the present results with those obtained for the mini-hairpins formed by d(mCGmCGTGmCG) and d(CGC"TAGCG) [5,36]. In these sequences, mC denotes a cytidine methylated at the C5 position and C" represents a cytidine in which the deoxyribose sugar is replaced by an arabinose sugar.…”
Section: Comparison With Other Hairpinsmentioning
confidence: 74%
“…e--(+-ccf-flyt instead of e'-C--a--fl-y+. nucleotide form a base pair, but in this case the second loop residue (the thymine) is turned into the minor groove [36] as in the d(ATCCTATTTATAGGAT) molecule. The presence of the arabinose sugar may be surmised to play a predominant role in inducing this effect, but the d(ATCCTATTTATAG-GAT) hairpin is an example that this may occur in an all deoxyribose-phosphate backbone as well.…”
Section: The Hairpin-loop Structurementioning
confidence: 99%
“…A DNA hairpin is made up of two parts: a base-paired stem and a single-stranded loop connecting the two halves of the stem. Structural studies have shown that the loop of fully complementary hairpins generally adopts a 2-or 4-unpaired-nucleotide structure, due to the tremendous steric constraints imposed by the bonding of the last two nucleotides (29,35,36). A DNA hairpin has therefore to be seen as a dynamic equilibrium adopting the more favorable energy conformation under a given steric stress.…”
Section: Discussionmentioning
confidence: 99%